Patterns of suicide deaths in Hungary between 1995 and 2017 - Tamás Lantos; Richard J.Q. McNally; Tibor András Nyári (Elsevier, 2021)
Hungary has had one of the highest suicide mortality rates in the world for decades. Investigating seasonality of suicide deaths is essential as its findings could be key elements in the prevention. In our study we have analyzed the seasonal effect in suicide mortality in relation to possible risk factors in Hungary during 1995-2017.Data on the numbers of suicide deaths were obtained from a published online database. Negative binomial regression was employed to investigate the effect of possible risk factors and seasonal and annual trends in suicide rates. The seasonal effect was further investigated, adding a significant risk factor from the "initial" negative binomial regression.The suicide risk was significantly (p < 0.001) higher in men than in women (incidence rate ratio: 3.48), and it increased with age and decreased with education level. Marriage was a protective factor against suicide. Annual suicide mortality declined significantly (p < 0.001 for trend) from 36.7 (95% confidence interval: 35.5-37.9) to 16.5 (15.7-17.3) per 100,000 persons per year during the study period. Significant seasonality was found in suicide rates with a peak in late June. Similar peaks were observed at each level of each risk factor. There were differences in peaks by suicide method. The peak of non-violent suicides was in early June; suicides committed by violent methods peaked half a month later.This study suggests that there was a significant seasonal effect on suicide deaths between 1995 and 2017, which remained significant even in the presence of each risk factor. To our knowledge, this has been the first study to investigate the seasonal pattern so extensively in Hungary. Our findings confirm that the environmental effects are involved in the etiology of suicide mortality.